Mosaic gene expression analysis of semaphorin–plexin interactions in Caenorhabditis elegans using the IR‐LEGO single‐cell gene induction system. (15th June 2022) - Suzuki, Motoshi; Nukazuka, Akira; Kamei, Yasuhiro; Yuba, Shunsuke; Oda, Yoichi; Takagi, Shin
Abstract: Genetic mosaic analysis is a powerful means of addressing the sites of gene action in multicellular organisms. In conventional genetic analysis, the generation of desired mosaic patterns is difficult to control due to the randomness of generating the genetic mosaic which often renders the analysis laborious and time consuming. The infrared laser–evoked gene operator (IR‐LEGO) microscope system facilitates genetic mosaic analysis by enabling gene induction in targeted single cells in a living organism. However, the level of gene induction is not controllable due to the usage of a heat‐shock promoter. Here, we applied IR‐LEGO to examine the cell–cell interactions mediated by semaphoring–plexin signaling in Caenorhabditis elegans by inducing wild‐type semaphorin/plexin in single cells within the population of mutant cells lacking the relevant proteins. We found that the cell contact–dependent termination of the extension of vulval precursor cells is elicited by the forward signaling mediated by the semaphorin receptor, PLX‐1, but not by the reverse signaling via the transmembrane semaphorin, SMP‐1. By utilizing Cre/loxP recombination coupled with the IR‐LEGO system to induce SMP‐1 at a physiological level, we found that SMP‐1 interacts with PLX‐1 only in trans upon contact between vulval precursor cells. In contrast, when overexpressed, SMP‐1 exhibits the ability to cis‐ interact with PLX‐1 on a single cell. These results indicate that mosaic analysis with IR‐LEGO, especially when combined with an in vivo recombination system, efficiently complements conventional methods. Abstract : Infrared‐laser‐evoked gene operator (IR‐LEGO) provides an opportunity to facilitate the genetic mosaic analysis by enabling gene induction in targeted single cells in a living organism. Here we apply IR‐LEGO to show that cell‐contact‐dependent termination of the extension of vulval precursor cells is elicited by the forward signaling mediated by the semaphorin receptor, PLX‐1, but not by the reverse signaling via the transmembrane semaphorin, SMP‐1.